The micro and macro of managerial beliefs - Barrero, Jose Maria (Journal of Financial Economics, 2022)
This paper studies how biases in managerial beliefs affect managerial decisions, firm performance, and the macroeconomy. Using a new survey of US managers I establish three facts. (1) Managers are not overoptimistic: sales growth forecasts on average do not exceed realizations. (2) Managers are overprecise: they underestimate future sales growth volatility. (3) Managers overextrapolate: their forecasts are too optimistic after positive shocks and too pessimistic after negative shocks. To quantify the implications, I estimate a dynamic general equilibrium model in which managers of heterogeneous firms use a subjective beliefs process to make forward-looking hiring decisions. Overprecision and overextrapolation lead managers to overreact to firm-level shocks and overspend on adjustment costs, destroying 2.1% to 6.8% of the typical firm’s value. Pervasive overreaction leads to excess volatility and reallocation, lowering consumer welfare by 0.5% to 2.3% relative to the rational-expectations equilibrium. These findings suggest overreaction could amplify asset-price and business-cycle fluctuations.